ANALYSIS OF THE EFFECT OF ISLAMIC LEADERSHIP ON TEACHER PERFORMANCE AT THE AL-MARWA COLLEGE FOUNDATION IN THE INDUSTRIAL REVOLUTION ERA 4.0 - Munawaroh, Munawaroh; Siregar, Horia; Fitria Jayusman, Sri; Zuriani Hsb, Melisa (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
Entering the era of the industrial revolution 4.0 has opportunities and challenges for schools around the world. The Al Marwa Foundation school is no exception. The Al Marwa college foundation must be able to survive in the midst of environmental changes and increasingly extraordinary competition. To be able to survive and achieve the vision, mission and goals of the foundation. Human resources have a very important role and function for the sustainability of education in the world. The purpose of this study was to determine the effect of Islamic leadership style on teacher performance at the Al Marwa Islamic boarding school foundation. This study uses a quantitative descriptive approach. The total population in this study were 30 respondents using a saturated sample. Data was collected by providing a list of statements to respondents, namely RA, MIS, and MDA teachers at the Al Marwa Islamic Boarding School Foundation. The results showed that the value of t arithmetic (3.776) > t table (1.701) this indicates that there is a positive effect. As for the significance value (0.001 < 0.05), the Islamic Leadership Style variable has a positive and significant impact on teacher performance at the Al Marwa College Foundation.